Research on Well-Being and Robotics in Education - Smyrnova-Trybulska Eugenia; Porczyńska-Ciszewska Anna; Kopczyński Tomasz; Kommers Piet (Studies in Logic, Grammar and Rhetoric)
Human mental well-being, measured by the frequency of experiencing happiness, may be one of the most important factors in supporting learning and stimulating creative thinking, so necessary during robotics and programming classes. Positive emotional states, mental well-being, and a sense of happiness are also closely related to social contacts, the development of which is undoubtedly contributed to by the participation of students in the performing of joint tasks during robotics and programming classes. The article presents the results of research on the relationship between mental well-being, the measure of which is the frequency of experiencing happiness, and the implementation of robotics and programming classes in high school. The study covered 127 high school students in southern Poland. The Happiness Experience Scale (SDS) and a questionnaire were used in the research. On the basis of the obtained research results, it can be concluded that experiencing happiness is related to the development of creativity and social competences among students participating in robotics and programming classes. The issue of robots in education as a part of STEM education was considered. Initial qualitative research was also done on the organization of robotics and programming classes.